2022
DOI: 10.3389/fvets.2022.855405
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inorganic Phosphorus Levels on Phosphorus Utilization, Local Bone-Derived Regulators, and BMP/MAPK Pathway in Primary Cultured Osteoblasts of Broiler Chicks

Abstract: Understanding the underlying mechanisms that regulate the bone phosphorus (P) utilization would be helpful for developing feasible strategies to improve utilization efficiency of P in poultry. We aimed to investigate the effects of inorganic P levels on P utilization, local bone-derived regulators and bone morphogenetic protein/mitogen-activated protein kinase (BMP/MAPK) pathway in primary cultured osteoblasts of broiler chicks in order to address whether local bone-derived regulators or BMP/MAPK pathway was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Furthermore, ERK1 inhibitor was shown to suppress the ALP activity, bone mineralization and downregulate the expression of BMP2 mRNA in mice bone mesenchymal stem cells ( 10 ). The results from our studies in vivo and in vitro have demonstrated that P utilization in the bone and osteoblasts of broilers might be partially regulated by BMP2 and ERK1 ( 11 , 12 ). However, it is unknown if BMP2 or ERK1 is directly involved in regulating P utilization in primary broiler osteoblasts.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, ERK1 inhibitor was shown to suppress the ALP activity, bone mineralization and downregulate the expression of BMP2 mRNA in mice bone mesenchymal stem cells ( 10 ). The results from our studies in vivo and in vitro have demonstrated that P utilization in the bone and osteoblasts of broilers might be partially regulated by BMP2 and ERK1 ( 11 , 12 ). However, it is unknown if BMP2 or ERK1 is directly involved in regulating P utilization in primary broiler osteoblasts.…”
Section: Introductionmentioning
confidence: 89%
“…At 24 h post-transfection, all cells were washed twice with the P-free DMEM medium to remove the residual P. Then, the normal cells and BMP2 or ERK1 silencing cells were incubated in the osteogenic induction medium (OIM) supplemented with 0.0 or 2.0 mmol/L of P for 12 days. Selecting the supplemental P dose of 2 mmol/L in the present study was based on our previous studies ( 11 , 13 ). The OIM was the P-free DMEM supplemented with 15% FBS, 1% penicillin/streptomycin, 1% L-glutamine, 100 nmol/L Dex and 50 μg/mL ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DMP1 has been found to be involved in regulating P homeostasis and bone mineralization in mammals ( 24 , 25 ). Latest studies in vivo and in vitro suggested that bone P retention or osteoblastic P utilization might be regulated by DMP1 ( 1 , 26 ), implying a possible contribution of DMP1 to the bone P utilization of broilers. However, whether DMP1 is involved in regulating P metabolic utilization in primary cultured tibial osteoblasts of broiler chicks has not been reported before.…”
Section: Introductionmentioning
confidence: 99%